DIGITAL MARKETING STRATEGIES FOR A DRINKING WATER BRAND - Chichulina, Kseniia; Dobryanska, Victoriia (European Science, 2025)
In the course of the research, we developed the layout of the main page of the site, since the company's site is not very informative and is not able to attract the attention of the consumer. The site should be filled with graphic materials, company news,